2011
DOI: 10.3144/expresspolymlett.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of block composition on thermal properties and melt viscosity of poly[2-(dimethylamino)ethyl methacrylate], poly(ethylene oxide) and poly(propylene oxide) block co-polymers

Abstract: Block co-polymers can have several properties that are not present in comparable statistical co-polymers, and interest in studying their properties has increased considerably during recent decade [1]. Block co-polymers can have, for example, the ability to form self-organized structures [2]. Especially co-polymers consisting of PDM (poly[2-(dimethylamino)ethyl methacrylate]), PEO (poly(ethylene oxide)), and/or PPO (poly(propylene oxide) blocks have found applications in the field of hydrophobizing paper [3] or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…Again, these favorable van der Waals interactions could be one reason for the miscibility of both polymers in the bulk, where hydrogen bonding and electrostatic interactions are negligible (as PPO and PDMAEMA lack charged sites and possible hydrogen bonding sites). 41 Obviously, a higher density of neighboring PPO and PDMAEMA units is required, since the diblock PPO 69 -b-PDMAEMA 100 does not show this behavior at low temperature. Interestingly, the diblock PPO 69 -b-PDMAEMA 100 shows an unexpected behavior at elevated temperatures with a broad, shouldered peak.…”
Section: Ir-spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Again, these favorable van der Waals interactions could be one reason for the miscibility of both polymers in the bulk, where hydrogen bonding and electrostatic interactions are negligible (as PPO and PDMAEMA lack charged sites and possible hydrogen bonding sites). 41 Obviously, a higher density of neighboring PPO and PDMAEMA units is required, since the diblock PPO 69 -b-PDMAEMA 100 does not show this behavior at low temperature. Interestingly, the diblock PPO 69 -b-PDMAEMA 100 shows an unexpected behavior at elevated temperatures with a broad, shouldered peak.…”
Section: Ir-spectroscopymentioning
confidence: 99%
“…Therefore, close contact of the PDMAEMA units with the PPO units is an immanent feature of the starshaped system leading locally to a situation similar to the situation in bulk mixtures. 41 The close contact triggers the weak, but favorable interactions between PPO and PDMAEMA, leading to a hydrophobic domain at the center of the star. Then, this domain can act as a nucleus for further complexation between PPO and PDMAEMA, as suggested by the IR-data.…”
Section: Scheme 1 Solution Behavior Of Diblock Copolymersmentioning
confidence: 99%
“…There are not many rheological studies on blending of PEO with a copolymer containing hard and soft segments [32,33]. Blends of PEO with natural rubber-graft-poly(methyl methacrylate) polymer (NR-g-PMMA) (mole ratio of NR and PMMA-graft polymer: 60%:40%), where the NR backbone is the soft segment and the PMMA-graft polymer is the hard segment, may serve as interesting polymer hosts for SPEs.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the cationic pentablock copolymer was performed by oxyanionic polymerization from the commercial PEG-b-PPO-b-PEG hydroxyl end capped polymer. [44] QCM-D experiments revealed that the cationic pentablock copolymer exhibited more irreversible binding to the cellulose surface than the triblock copolymer. It was suggested that the most important segment of the polymer for binding to the cellulose surface was the qPDMAEMA blocks.…”
Section: Figmentioning
confidence: 98%